KAJIAN YURIDIS TERHADAP KEWENANGAN BANK INDONESIA DAN LEMBAGA PENJAMIN SIMPANAN DALAM MELAKUKAN PENANGANAN TERHADAP BANK GAGAL YANG TIDAK BERDAMPAK SISTEMIK - Dhita Kusuma, Wira; Putra Atmadja, Ida Bagus; Rudy, Dewa Gde (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 02, Februari 2013, 2013)
In addition to deposit guarantee, Deposit Insurance Corporation also authorized to deal with Failing Bank, both of Systemic Effect and Non-Systemic Effect. Where the same authority held by Bank Indonesia. So, how does the authority between Bank Indonesia and Deposit Insurance Corporation in handling Failing Bank which are Non- Systemic Effect and how the process of handling by the authorities of the Deposit Insurance Corporation. The research method used is Normative Legal Research, the type of approach used are the Statute Approach and Comparative Approach. Legal material source used by the primary and secondary legal materials. Technique collection of legal materials based on the Library Research and from the laws that have been obtained to use Technical Analysis Argument and Systematization to get relevant answers to the issues raised. The authority to handle Failing Bank arranged in two laws, namely Article 37 paragraph (2) of the Banking Act and Article 26 of the Deposit Insurance Corporation Act. While the stages of handling Failing Bank of Non- Systemict Effect by Deposit Insurance Corporation regulated in Article 22 to Article 30 of the Act Deposit Insurance Corporation. With the two legislation that have the same authority to regulate handling Bank Failing of Non-Systemic Effect, may result in a contradiction or conflict between Bank Indonesia and Deposit Insurance Corporation in any treatment for the Failing Bank.
Keywords: Bank Indonesia, Deposit Insurance Corporation, Failing Bank, Non- Systemic Effect